Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Guru SMPN di Kecamatan Pauh Duo Kabupaten Solok Selatan - Mandra Adrika Putra; Reviana Novita (JURNAL ADMINISTRASI KANTOR, 2025)
The purpose of this study was to measure and analyze the effect of training and work motivation on the performance of public junior high school teachers in Pauh Duo District, South Solok Regency. This study was conducted on civil servant (PNS) and non-civil servant (PNS) teachers of junior high schools in Pauh Duo District, South Solok Regency. This study used descriptive and causal methods, which consisted of two independent variables (training and motivation) and one dependent variable (performance). Respondents in this study were all civil servant and non-civil servant teachers of junior high schools in Pauh Duo District, South Solok Regency, totaling 60 respondents selected using saturated sampling techniques. The sources used consisted of primary and secondary data collected through observation, literature study (documentation) and questionnaire distribution. The analytical tool used in this study was the SEM (Structural Equation Model) method based on PLS (Partial Least Square). The results showed that training had a positive and significant effect on teacher performance (O = 0.382; T = 3.222; P < 0.05). Work motivation also has a positive and significant effect on teacher performance (O = 0.536; T = 0.330; P < 0.05). Thus, training and work motivation significantly improve teacher performance. Keywords: Training, Work Motivation, Performance.